Social innovation and new business models creating shared value in low-income markets - Michelini, Laura (SpringerBriefs in Business, 2012)
Extreme poverty continues to afflict the world, and it requires urgent action. Social innovation can be the driving force to spark change and to find common ground for shared value creation, particularly when it is directed at low-income markets. Leading companies have recently developed innovative forms of social innovation by combining three elements - the concept of shared value creation, the theory of the fortune at the bottom of the pyramid, and a corporate social entrepreneurship approach - which they use to enter low-income markets by helping to solve global challenges while simultaneously generating profits.The book identifies the main forms of social innovation: social business models, social products and social communication strategies. Further, it shows how companies can successfully implement social innovation and presents new forms of social business models that can be used to target low-income markets. Finally, the book presents key success factors related to the social product innovation process and corresponding communication.